Women Judges and Women’s Rights in Pakistan - Holden, Livia (Oñati Socio-Legal Series, 2017)
Although the first appointment of women judges in Pakistan dates back to 1974, the massive appointment of "lady judges" in the past decade has caused a jump in female representation in the judiciary to more than one third - a quiet move that sends a message of adherence to the principle of gender equality as per the international treaties to which Pakistan is signatory. By investigating the everyday interactions and preoccupations of women-judges in their daily management of justice, this paper explores the socio-legal reception of the human rights discourse from the perspective of the female judges. The challenge in this scenario lies, on the one hand, in whether this change will be only formal or will also lead to substantial and accountable justice and, on the other hand, how the global agenda impacts local expectations and conceptualizations of rights within and beyond the state.